Search for electroweak production of supersymmetric particles in final states with two or three leptons at $\sqrt{s}=13\,$TeV with the ATLAS detector - ATLAS collaboration (2880 authors); Aguilar-Saavedra, Juan Antonio; Amor Dos Santos, Susana Patricia; Anjos, Nuno; Araque, Juan Pedro; Castro, Nuno Filipe; Conde Mui\~no, Patricia; Da Cunha Sargedas De Sousa, Mario Jose; Fiolhais, Miguel; Galhardo, Bruno; Gomes, Agostinho; Gon\c calo, Ricardo; et al. (My University, 2018)
A search for the electroweak production of charginos, neutralinos and sleptons decaying into final states involving two or three electrons or muons is presented. The analysis is based on 36.1 fb$^{-1}$ of $\sqrt{s}=13$ TeV proton--proton collisions recorded by the ATLAS detector at the Large Hadron Collider. Several scenarios based on simplified models are considered. These include the associated production of the next-to-lightest neutralino and the lightest chargino, followed by their decays into final states with leptons and the lightest neutralino via either sleptons or Standard Model gauge bosons; direct production of chargino pairs, which in turn decay into leptons and the lightest neutralino via intermediate sleptons; and slepton pair production, where each slepton decays directly into the lightest neutralino and a lepton. No significant deviations from the Standard Model expectation are observed and stringent limits at 95% confidence level are placed on the masses of relevant supersymmetric particles in each of these scenarios. For a massless lightest neutralino, masses up to 580 GeV are excluded for the associated production of the next-to-lightest neutralino and the lightest chargino, assuming gauge-boson mediated decays, whereas for slepton-pair production masses up to 500 GeV are excluded assuming three generations of mass-degenerate sleptons.